Clustering Algorithms in Data Mining: A Comprehensive Study - Kaur, Jaskaranjit; Kaur, Gurpreet (International Journal of Computer Sciences and Engineering, 2025)
Distribution of dataset into a set of homogeneous clusters is the elementary operation in data mining. Clustering is the key technique of distribution in data mining. Clustering is the method of grouping data objects in such a way that the data objects in the same cluster are more similar (intra-cluster similarity) to each other and are less similar to data objects in other cluster (inter-cluster similarity). Clustering can be done with different algorithms. In this review paper, a survey of clustering and its different techniques is done. This paper covers some of the partitioning and hierarchical clustering algorithms.